Theoretical and methodological reasoning of correction technologies of the physical conditions of students of music speciality - Marynchuk, Petro (Journal of Education, Health and Sport, 2017)
The article emphasizes the lack of development of the methodological basis for the physical education of students of Music Arts. Professionally dependent indicators of physical condition were taken into account. The article also outlines the main theoretical and methodological provisions that underlie the development of technology for correction of the physical condition of students of music arts. They are in particular actualization of life-giving motivation of students to increase the level of physical condition, regular physical exercises, the need for the development of professionally important physical qualities, ensuring the differentiation of physical activity, taking into account the level of physical state and physical conditions of students of Music Arts. The structure of the technology of correction of the physical condition of students of Music Arts is considered. The technology contains the purpose, tasks, principles, stages of implementation, the program with the use of physical culture, performance criteria. The main stages of the technology implementation – preparatory, main, final – are analyzed. The means of motor activity of innovative direction are described for use in the practice of higher educational institutions, which take into account the features of the student staff, their mode of educational activity.